DETERMINATION OF THE OPTIMAL CONDITIONS FOR THE SPECTROPHOTOMETRIC DETERMINATION OF Ni(II) IONS USING 7- BROMO-2-NITROSO-1-OXYNAPHTHALENE-3,6-DISULFOXIDE - Nazirov Sh.S,; Turaev Kh.Kh, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, the spectrophotometric detection method of complexing Ni(II)  ion  with  7-bromo-2-nitroso-1-oxynaphthalene-3,6-disulfoacid  (BNOKS-S,  S-3,6) (HR) with organic analytical reagent developed and studied optimal conditions: λ max  =  640,  pH  =  6,5,  universal  buffer,  reagent  -  buffer  -  Ni(II)  -  distilled  water, BNOKS-S with 0.05% relative to T Ni2+ =10 μg/25ml, 1.0 ml of S-3.6 reagent was found to  be  sufficient.  The  area  of  obedience  to  the  Bouguer-Lambert-Behr  law  was determined  to  be  1.0-17.5  μg/25  ml.  Absorption  spectra  were  studied:  sensitivity according to Sendel was 0.0011 μg/cm2, contrast ∆λ = 100 nm.